Estimasi Emisi CO2 dari Aktivitas Permukiman di Kelurahan Aur Kenali Kota Jambi - Ilham Akbar; Anggrika Riyanti; Siti Umi kalsum; Peppy Herawati (Universitas Batanghari Jambi, 2026)
The escalation of Greenhouse Gas (GHG) emissions, particularly carbon dioxide (CO₂), has become a critical global climate change issue with significant implications for Indonesia. This study quantifies CO₂ emissions from household activities in Aur Kenali, Jambi City, covering electricity consumption, LPG usage, transportation, and waste management. Using a descriptive quantitative approach with 100 respondents, the data were analyzed based on the 2006 IPCC guidelines.The results reveal a total emission of 47.02 tons CO₂-eq from the sampled households. The primary contributor is electricity consumption at 23.14 tons CO₂-eq (49.21%), followed by transportation at 15.39 tons CO₂-eq (32.73%), waste management at 5.35 tons CO₂-eq (11.38%), and LPG usage at 3.14 tons CO₂-eq (6.68%). These findings indicate that electricity usage is the dominant emission source in the study area, highlighting the urgent need for enhanced environmental education to foster more sustainable community behavioral changes.